2019
DOI: 10.1111/jph.12798
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of new nematicides for managing Meloidogyne incognita in tomato crop

Abstract: New non-fumigant nematicides (fluensulfone, fluopyram and fluazaindolizine) were tested in greenhouse tomato trials aiming to evaluate its efficacy on the control of Meloidogyne incognita soil and root populations and plant produtivity. Plants of the cultivar Red Gnome were transplanted into 2,500 cm 3 fibre pots inoculated with 200 eggs of M. incognita/100 cm 3 of soil and treated with fluensulfone, fluopyram and fluazaindolizine, in two rates each. After eight weeks of incubation the plants were evaluated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…At sublethal doses fluazaindolizine and fluensulfone suppressed M. incognita reproduction more than fluopyram, although actual sublethal doses were much lower for the latter ( Thoden and Wiles, 2019 ; Wram and Zasada, 2019 ). In another study, half and full labeled rates of any of these compounds did not suppress reproduction of M. incognita ( Silva et al, 2019 ).…”
Section: Efficacy Of New Chemical Nematicides In Greenhouse and Fieldmentioning
confidence: 90%
“…At sublethal doses fluazaindolizine and fluensulfone suppressed M. incognita reproduction more than fluopyram, although actual sublethal doses were much lower for the latter ( Thoden and Wiles, 2019 ; Wram and Zasada, 2019 ). In another study, half and full labeled rates of any of these compounds did not suppress reproduction of M. incognita ( Silva et al, 2019 ).…”
Section: Efficacy Of New Chemical Nematicides In Greenhouse and Fieldmentioning
confidence: 90%
“…In 2014, fluopyram was registered as a seed treatment to control the soybean cyst nematode, Heterodera glycines ( Beeman and Tylka, 2018 ). Currently available studies also demonstrated how fluopyram affects the development of the nematodes species, M. incognita , M. javanica , H. glycines , H. schachtii , and Pratylenchis loosi ( Hurd et al, 2015 ; Kim et al, 2016 ; Beeman and Tylka, 2018 ; Mohotti et al, 2018 ; Dahlin et al, 2019 ; Hajihassani et al, 2019 ; Ji et al, 2019 ; Oka and Saroya, 2019 ; Schleker et al, 2019 ; Silva et al, 2019 ).…”
mentioning
confidence: 99%
“…Fluopyram nematicide was not effective for managing plant-parasitic nematode populations at 50 or more days after planting in this study as it had no effect on ring nematode population density and increased spiral and RN population densities at various times compared with untreated control. Previous studies have found that fluopyram can be effective against other nematodes, including root-knot nematodes on vegetables ( Hajihassani et al, 2019 ; Ji et al, 2019 ; Silva et al, 2019 ) and cotton ( Roper, 2017 ) as well as a mixture of sting nematode ( Belonolaimus longicaudatus ) and spiral nematodes on turfgrass ( Waldo et al, 2019 ). The concentration of fluopyram needed to paralyze nematodes in vitro is greater for RN than M. incognita ( Faske and Hurd, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…While effective in managing Meloidogyne spp. on vegetables in greenhouse and microplot studies ( Hajihassani et al, 2019 ; Silva et al, 2019 ), evaluation of fluopyram effects on other plant-parasitic nematodes is needed in various rotation systems.…”
mentioning
confidence: 99%